Investigating the cardiorespiratory fitness gene COX7A2L in cardiomyocytes: Viability and mitochondrial function - Ada Nilsen Nordeidet; Gurdeep S. A. Marwarha; Øystein Røsand; Victoria Johansen; Karin Garten; Morten A. Høydal; Mette Langaas; Anja Bye (PLoS ONE, 2025)
Low cardiorespiratory fitness (CRF) is a well-established risk factor for cardiovascular disease (CVD) and all-cause mortality. Since CRF is largely genetically determined, understanding the genetic influences on CRF might reveal the protective mechanisms of high CRF. One gene found to be associated with CRF is COX7A2L. COX7A2L is a mitochondrial supercomplex assembly factor, but its role in cellular metabolism remains a topic of discussion. We hypothesized that COX7A2L could play a role in cellular respiration in cardiomyocytes, affecting cardiac function and CRF. To determine the effect of COX7A2L on cardiomyocyte function, we overexpressed and knocked down COX7A2L in human AC16 cardiomyocytes and performed MTT assays and Seahorse XF Cell Mito Stress Tests to assess cell viability and mitochondrial function. For the mitochondrial function measurements, we stimulated the cells with isoproterenol to investigate if the effect of altering COX7A2L levels would be larger under simulated increased energy demand. Overexpression and knockdown were validated using sandwich ELISA. Our findings showed that altering COX7A2L expression in human AC16 cardiomyocytes did not significantly affect cell viability or mitochondrial function. Further research is necessary to determine whether COX7A2L influences cardiomyocyte function and CRF.